Conjunctival Mycobacteriosis - Nastiti N. Rahajoe; Darmawan B. Setyanto; Muhammad Rhum; Tetty A. Usman (Paediatrica Indonesiana, 1993)
A 6 1/2- year old Indonesian girl with 30 kg of body weight was consulted to the Department of Child Health, Cipto Mangunkusumo Hospital - Medical School University of Indonesia , Jakarta, for eye, surgery tolerance. At 3 1/2 years old, she came for the first time with a granulomatous tumor on her left eye. Excision was done, and histopathologic examination revealed granulation tissue corresponding to tuberculosis. The patient was referred to the Department of Child Health for further exploration. Sensitin test was positive for Mycobacterium intracellulare, not for Mycobacterium tuberculosis. The tumor reappeared twice and the last histopathologic examination revealed nonspecific granulation tissue.